Islamic banks’ service quality in Somalia: Customer loyalty, satisfaction, and the role of trust as a mediator - Barre, Galad Mohamed; Warsame, Abdimalik Ali; Hussein, Hassan Abdikadir; Mohamed, Ismail Ibrahim (Asian Economic and Financial Review, 2023)
The purpose of this study is to assess how the PAKSERV paradigm affects brand loyalty, customer satisfaction, and trust in Somalia’s banking industry. With an emphasis on the mediating function of trust in the Somali scenario, these comprehensive assessments stress the cultural component of quality of service. This study adopts a quantitative method by assessing 370 Islamic bank customers in Somalia for two main cities, Mogadishu and Hargeisa. Our respondents are existing and potential users of Islamic bank products and the sample was selected using the convenience sample technique. The data were examined with the quantitative method of structural equation modeling using SmartPLS 3.3.7. The study found a connection between client satisfaction, loyalty, and the PAKSERV quality of service attributes through the intermediary role of trust. In the cultural context of Islamic finance in Somalia, this study offers fresh information on how trust may function as a partial mediator in the interaction between client satisfaction and customer loyalty.